Pengembangan Papan Make and Match sebagai Media Penguasaan Multi-Literasi Peserta Didik TK - Sari, Arviani; Ngatmini, Ngatmini; Siswanto, Joko (Universitas PGRI Semarang, 2023)
Learning media is one of the important components used in learning activities. Good learning media can help students achieve competence. Based on observations, it is known that the multiliteracy abilities of group B students of TK Masyitoh Karangasem Batang such as: the ability to read, write and count are not maximized, teachers in providing learning still use conventional methods, as a result many students experience boredom and boredom. boredom is a natural thing especially learning that tends to be monotonous. The feeling of boredom and saturation that comes is not good and will greatly affect the learning process of students. If you are bored then someone will be lazy to do it. If the feeling of laziness in learning is left longer, the result is that the achievement and academic value of students will certainly decrease.This study aims to describe the validity of the make and match board which was developed as a medium for mastering multiliteracy for kindergarten students. describe the practicality of the make and match board which was developed as a medium for mastering multiliteracy for kindergarten students.This study uses a 4D development research approach adapted from the Thiagarajan and Semmel development model with 3 steps: 1) Define (defining); (2) Design (design); (3) Develop (development). Data collection techniques were carried out by tests, observations, questionnaires, interviews and documentation. The data analysis technique uses product data analysis, initial data analysis, t test and gain test.The results showed that the make and match board was feasible to use with the results of the validity test using aiken V in the medium and high categories and the reliability test in the strong category. make and match boards are feasible to be effectively used in learning, it is known that based on learning outcomes there is an average difference through the t test of -10.578 and an average increase (gain) of 0.535 which based on the interpretation of the gain index is classified as moderate.The conclusion of this research is that the make and match board is feasible and effective to use in learning, especially in mastering multi-literacy materials to explore new knowledge from the make and match board media. Teachers are expected to be able to develop make and match boards that are similar to different materials, and the school is expected to facilitate.